2019
DOI: 10.1007/978-3-030-33220-4_13
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy Extraction for Customer Service Knowledge Base Construction

Abstract: Customer service agents play an important role in bridging the gap between customers' vocabulary and business terms. In a scenario where organisations are moving into semi-automatic customer service, semantic technologies with capacity to bridge this gap become a necessity. In this paper we explore the use of automatic taxonomy extraction from text as a means to reconstruct a customer-agent taxonomic vocabulary. We evaluate our proposed solution in an industry use case scenario in the financial domain and show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…The process of extracting a knowledge graph is essentially the same as that of ontology learning [12] and consists of three main stages: firstly, the relevant entities or terms must be identified, in a process called automatic term recognition, then the relations between these terms must be constructed, and finally, these must be organized into a single coherent knowledge graph. For the first task of extracting terms, a number of heuristic methods have been developed based on the frequency of terms and syntactic patterns [2,13,14]. Relation extraction approaches were initially based on the discovery of patterns that are indicative of relations, such as the patterns proposed by Hearst [15]; however, recently, new distributional methods have become popular for extracting relations [16], which rely on word embeddings to predict relations between entities, and authors have explored combining pattern-based and distributional methods [17] or extending the results to multiple relations [18].…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…The process of extracting a knowledge graph is essentially the same as that of ontology learning [12] and consists of three main stages: firstly, the relevant entities or terms must be identified, in a process called automatic term recognition, then the relations between these terms must be constructed, and finally, these must be organized into a single coherent knowledge graph. For the first task of extracting terms, a number of heuristic methods have been developed based on the frequency of terms and syntactic patterns [2,13,14]. Relation extraction approaches were initially based on the discovery of patterns that are indicative of relations, such as the patterns proposed by Hearst [15]; however, recently, new distributional methods have become popular for extracting relations [16], which rely on word embeddings to predict relations between entities, and authors have explored combining pattern-based and distributional methods [17] or extending the results to multiple relations [18].…”
Section: Related Workmentioning
confidence: 99%
“…Relation extraction approaches were initially based on the discovery of patterns that are indicative of relations, such as the patterns proposed by Hearst [15]; however, recently, new distributional methods have become popular for extracting relations [16], which rely on word embeddings to predict relations between entities, and authors have explored combining pattern-based and distributional methods [17] or extending the results to multiple relations [18]. Taxonomy construction extends the task of term and relation extraction to a holistic approach, and initial results have shown that this is a very hard task [19]; until recently, very few approaches have improved on the state-of-the-art [2,20].…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations